2016
DOI: 10.1016/j.jjcc.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Major cardiac event risk scores estimated with gated myocardial perfusion imaging in Japanese patients with coronary artery disease

Abstract: The risk scores obtained from this study are useful to predict MCEs in Japanese patients with CAD and are expected to be useful for management and informed consent of high-risk CAD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…5,21) LVEF is one of the predictors useful in the estimation of MCE risks with the Heart Risk Table. However, in a previous study, 10) we found that LVEF was an independent significant predictor of cardiac death but not of MCEs. Therefore, we have separately prepared two different equations to predict the risks of MCEs and cardiac death.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…5,21) LVEF is one of the predictors useful in the estimation of MCE risks with the Heart Risk Table. However, in a previous study, 10) we found that LVEF was an independent significant predictor of cardiac death but not of MCEs. Therefore, we have separately prepared two different equations to predict the risks of MCEs and cardiac death.…”
Section: Discussioncontrasting
confidence: 65%
“…All study participants provided written informed consent prior to inclusion in the study. Tctetrofosmin myocardial perfusion SPECT 8,[10][11][12][13][14][15][16] at Nihon University Itabashi Hospital between October 2004 and March 2013 and who had a significant stenosis with 75% or greater narrowing of the arterial diameter detected by coronary angiography (CAG) performed after confirmation of at least 5% ischemia by the SPECT. The patients underwent treatment including revascularization and medication, and thereafter, were re-evaluated with the SPECT during a chronic phase and followed up to confirm prognosis for at least one year.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore we performed a three-year prognostic follow-up study in 2,579 patients who underwent myocardial perfusion SPECT in our hospital to prepare a regression equation suitable to predict the risk of MCEs excepting heart failure and reported our original cardiac event risk score (CERS) [39]. The following is a description of the creation of the CERS according to our report.…”
Section: Management Of Cad On the Basis Of Future Cardiac Event Ratesmentioning
confidence: 99%